1991
DOI: 10.1073/pnas.88.16.6936
|View full text |Cite
|
Sign up to set email alerts
|

Change in the expression of a nuclear matrix-associated protein is correlated with cellular transformation.

Abstract: We have identified a monoclonal antibody that recognizes a nuclear matrix-associated protein in NIH 3T3 cells. The immunofluorescence pattern consists predominantly of bright nuclear granule clusters distributed throughout the nucleoplasm, with the exclusion of nucleoli. It recognizes a protein of 190 kDa that is down-regulated to various degrees in a panel of single-oncogene-transformed NIH 3T3 cells. Its localization is similar, but not identical, to the spliceosomal speckles. p190 shows a coordinate express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…To start the identification of general modulating factors of chromatin superstructure we have recently carried out the protein characterization of the NM-IF complex during rat hepatocyte transformation; we have found that the protein composition undergoes progressive changes synchronous with chromatin decondensation . The new synthesis of NM proteins relating to the emergence of successive cell populations was observed, in line with the contention that a subset of NM proteins is characteristic of the stage of transformation [Pienta et al, 1989;Brancolini and Schneider, 1991]. The actual relationship between chromatin decondensation phenomena and alterations in the composition and/or architecture of the NM still remains to be discovered.…”
mentioning
confidence: 53%
“…To start the identification of general modulating factors of chromatin superstructure we have recently carried out the protein characterization of the NM-IF complex during rat hepatocyte transformation; we have found that the protein composition undergoes progressive changes synchronous with chromatin decondensation . The new synthesis of NM proteins relating to the emergence of successive cell populations was observed, in line with the contention that a subset of NM proteins is characteristic of the stage of transformation [Pienta et al, 1989;Brancolini and Schneider, 1991]. The actual relationship between chromatin decondensation phenomena and alterations in the composition and/or architecture of the NM still remains to be discovered.…”
mentioning
confidence: 53%
“…Reports from several laboratories have shown that when the matrix is prepared in situ from adherentgrowing cells (Staufenbiel and Deppert 1984) the distinctive fluorescent pattern given by antibodies directed against nuclear antigens which resist extraction with high ionic strength buffers and nuclease digestion is identical to that detected in whole cells (e.g. Brancolini and Schneider 1991;Hirose et al 1988;Kallajoki et al 1991;Philopova et al 1987). These observations have been interpreted as meaning that cells actually contained an inner network acting as a nucleoskeleton.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, intensive studies have also suggested possibly related role(s) of the nuclear matrix in tumor progression (10 -16). In cancer cells, some transforming proteins appear to be associated with the matrix (23,24), and there are also indications of specific alterations in the protein composition of the matrix as cells undergo differentiation (25) and during the invasion and proliferation of tumors (14,15,24,25,42,43). Could a "tumor-specific" NMP be involved in a transition associated with tumor progression?…”
Section: Discussionmentioning
confidence: 99%